Cotter, Christopher. 2020. The Critical Study of Non-Religion: Discourse, Identity and Locality - Yates, Samuel Robert (Fieldwork in religion, 2021)
Cotter, Christopher. 2020. The Critical Study of Non-Religion: Discourse, Identity and Locality. London: Bloomsbury. ix + 211 pp. ISBN: 978-1-3500-9524-3 £76.50 (hbk)